Ethics of Learning in the Perspective of Scholars: Etika Belajar Dalam Perspektif Ulama - Azizah, Wafia; Astutik, Anita Puji (Indonesian Journal of Education Methods Development, 2023)
In today's era, juvenile delinquency is rife in the external environment and in the world of education. This study aims to determine the concept of learning ethics according to Islam and according to Shaykh Az-Zarnuji. This research is a type of library research, research whose object of study uses library data in the form of books. This research was conducted by reading, reviewing, and analyzing various literature articles, journals and books of Ta'limul Muta'alim. The results of this study Ethics in the teaching and learning process is clear as the selection of attitudes in the learning process that will determine the outcome of education, while according to Sheikh Az-Zarnûjî learning morals include: Intention, choosing knowledge, teachers, friends, steadfastness in learning, respect for knowledge and scholars, seriousness, perseverance, interest in learning, beginning of learning, learning discipline, trust in learning, and wara‟ in learning. study.